Structural and functional analysis of a conjugated bile salt hydrolase from Bifidobacterium longum reveals an evolutionary relationship with penicillin V acylase - Kumar, R. Suresh; Brannigan, James A.; Prabhune, Asmita; Pundle, Archana V.; Dodson, Guy G.; Dodson, Eleanor J.; Suresh, C. G. (Journal of Biological Chemistry, 2006)
Bile salt hydrolase (BSH) is an enzyme produced by the intestinal microflora that catalyzes the deconjugation of glycine- or taurine-linked bile salts. The crystal structure of BSH reported here from Bifidobacterium longum reveals that it is a member of N-terminal nucleophil hydrolase structural superfamily possessing the characteristic alpha beta beta alpha tetra-lamellar tertiary structure arrangement. Site-directed mutagenesis of the catalytic nucleophil residue, however, shows that it has no role in zymogen processing into its corresponding active form. Substrate specificity was studied using Michaelis-Menten and inhibition kinetics and fluorescence spectroscopy. These data were compared with the specificity profile of BSH from Clostridium perfrigens and pencillin V acylase from Bacillus sphaericus, for both of which the three-dimensional structures are available. Comparative analysis shows a gradation in activity toward common substrates, throwing light on a possible common route toward the evolution of pencillin V acylase and BSH.

Characterization of a new bacillus cereus ATUAVP1846 strain producing penicillin V acylase, and optimization of fermentation parameters - Sunder, Avinash Vellore; Kumar, Atul; Naik, Neha; Pundle, Archana V. (Annals of Microbiology, 2012)
Penicillin acylases are involved chiefly in the industrial production of semisynthetic penicillins, which remain the most widely used group of antibiotics. We have isolated a new bacterial strain ATUAVP1846 that produces penicillin V acylase (PVA). Phylogenetic analysis using 16S rRNA sequencing showed 99.37% homology with Bacillus cereus. Maximum PVA production was observed with B. cereus ATUAVP1846 at 30A degrees C, pH 7 after 24 h fermentation time under submerged conditions. Highest enzyme productivity was achieved using sucrose as carbon source, and tryptone and ammonium hydrogen phosphate as nitrogen sources. Minimal medium containing 0.4% glucose and 0.3% ammonium hydrogen phosphate was found to be optimal for maximum PVA production from B. cereus ATUAVP1846. The crude enzyme from B. cereus ATUAVP1846 was partially purified using ammonium sulfate fractionation and showed highest enzymatic activity in the hydrolysis of penicillin V at 40A degrees C and pH 6. The crude enzyme preparation also showed unique substrate specificity, preferring ampicillin and cephalexin over penicillin V.
Keywords: 16S rRNA; Bacillus cereus; isolation; Ntn hydrolase; Optimization; Penicillin acylase

Purification and characterization of YxeI, a penicillin acylase from Bacillus subtilis - Rathinaswamy, Priya; Gaikwad, Sushama M.; Suresh, C. G.; Prabhune, Asmita; Brannigan, James A.; Dodson, Guy G.; Pundle, Archana V. (International Journal of Biological Macromolecules, 2012)
The paper reports the purification and characterization of the first penicillin acylase from Bacillus subtilis. YxeI, the protein annotated as hypothetical, coded by the gene yxeI in the open reading frame between iol and hut operons in B. subtilis was cloned and expressed in Eshcherichia coli, purified and characterized. The purified protein showed measurable penicillin acylase activity with penicillin V. The enzyme was a homotetramer of 148 kDa. The apparent Km of the enzyme for penicillin V and the synthetic substrate 2-nitro-5-(phenoxyacetamido)-benzoic acid was 40 mM and 0.63 mM, respectively, and the association constants were 8.93 x 10(2) M-1 and 2.51 x 10(5) M-1, respectively. It was inhibited by cephalosporins and conjugated bile salts, substrates of the closely related bile acid hydrolases. It had good sequence homology with other penicillin V acylases and conjugated bile acid hydrolases, members of the Ntn hydrolase family. The N-terminal nucleophile was a cysteine which is revealed by a simple removal of N-formyl-methionine. The activity of the protein was affected by high temperature, acidic pH and the presence of the denaturant guanidine hydrochloride. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bacillus subtilis; Conjugated bile acid hydrolases; Ntn hydrolase; Penicillin acylase

Structural modelling of substrate binding and inhibition in penicillin V acylase from pectobacterium atrosepticum - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Suresh, C. G.; Pundle, Archana V.; Ramasamy, Sureshkumar (Biochemical and Biophysical Research Communications, 2013)
Penicillin V acylases (PVAs) and bile salt hydrolases (BSHs) have considerable sequence and structural similarity; however, they vary significantly in their substrate specificity. We have identified a PVA from a Gram-negative organism, Pectobacterium atrosepticum (PaPVA) that turned out to be a remote homolog of the PVAs and BSHs reported earlier. Even though the active site residues were conserved in PaPVA it showed high specificity towards penV and interestingly the penV acylase activity was inhibited by bile salts. Comparative modelling and docking studies were carried out to understand the structural differences of the binding site that confer this characteristic property. We show that PaPVA exhibits significant differences in structure, which are in contrast to those of known PVAs and such enzymes from Gram-negative bacteria require further investigation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bile salt hydrolase; docking; Homology modelling; Inhibition; Pectobacterium; Penicillin acylase